Chondrogenically Primed Human Mesenchymal Stem Cells Persist and Undergo Early Stages of Endochondral Ossification in an Immunocompetent Xenogeneic Model - Fahy, Niamh; Palomares Cabeza, Virginia; Lolli, Andrea; Witte-Bouma, Janneke; Merino, Ana; Ridwan, Yanto; Wolvius, Eppo B.; Hoogduijn, Martin J.; Farrell, Eric; Brama, Pieter A. J. (Frontiers in Immunology, 2021)
Tissue engineering approaches using progenitor cells such as mesenchymal stromal cells (MSCs), represent a promising strategy to regenerate bone. Previous work has demonstrated the potential of chondrogenically-primed human MSCs to recapitulate the process of endochondral ossification and form mature bone in vivo, using immunodeficient xenogeneic models. To further the translation of such MSC-based approaches, additional investigation is required to understand the impact of interactions between human MSC-constructs and host immune cells upon the success of MSC-mediated bone formation. Although human MSCs are considered hypoimmunogenic, the potential of chondrogenically-primed human MSCs to induce immunogenic responses in vivo, as well as the efficacy of MSC-mediated ectopic bone formation in the presence of fully competent immune system requires further elucidation. Therefore, the aim of this study was to investigate the capacity of chondrogenically-primed human MSC constructs to persist and undergo the process of endochondral ossification in an immune competent xenogeneic model. Chondrogenically differentiated human MSC pellets were subcutaneously implanted to wild type BALB/c mice and retrieved at 2 and 12 weeks post-implantation. The percentages of CD4+ and CD8+ T cells, B cells and classical/non-classical monocyte subsets were not altered in peripheral blood of mice that received chondrogenic-MSC constructs compared to sham-operated controls at 2 weeks post-surgery. However, MSC-implanted mice had significantly higher levels of serum total IgG compared to sham-operated mice at this timepoint. Flow cytometric analysis of retrieved MSC-constructs identified the presence of T cells and macrophages at 2 and 12 weeks post-implantation, with low levels of immune cell infiltration to implanted MSC constructs detected by CD45 and CD3 immunohistochemical staining. Despite the presence of immune cells in the tissue, MSC constructs persisted in vivo and were not degraded/resorbed. Furthermore, constructs became mineralised, with longitudinal micro-computed tomography imaging revealing an increase in mineralised tissue volume from 4 weeks post-implantation until the experimental endpoint at 12 weeks. These findings indicate that chondrogenically differentiated human MSC pellets can persist and undergo early stages of endochondral ossification following subcutaneous implantation in an immunocompetent xenogeneic model. This scaffold-free model may be further extrapolated to provide mechanistic insight to osteoimmunological processes regulating bone regeneration and homeostasis.